Cogeneration and Clean Air - Mekhriya A. Koroli; Bekzod B. Oppokhuzhaev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2024)
Relevance: at present, the fuel and energy complex of the republic is experiencing a crisis. The main manifestation of the crisis is that disruptions and interruptions in the supply of fuel, electricity and heat to individual regions and consumers are becoming commonplace. One of the most promising solutions to the current situation is the development of small-scale energy. The process of joint generation of electricity and heat - cogeneration has great potential here, which, among other things, provides an opportunity for the development of the country's economy. Aim: to show by calculating emissions of pollutants that the combined production of electricity and heat, i.e. cogeneration, does not lead to excess air pollution. Methods: calculation of emissions of pollutants and dry flue gases, as well as comparative analysis with regulatory data. Results: the introduction of mini-Thermal power plant, in addition to its technological advantages in saving money and energy, environmental safety, provides significant prospects for the development of the energy sector of the region and an increase in the entire economy of the state as a whole. At the same time, the concentration of all pollutants formed during combustion of natural gas are within the quotas permitted.